'Where all the paperwork's done': Pynchon's critique of contracts. Issue 3 (16th March 2019) - Severs, Jeffrey
ABSTRACT: In his attitudes toward his book deals, his critiques of weapons-makers and other corporations, and his thinking about the possibility of a U.S. social contract within a neoliberal era that undermines it, Pynchon has across his career played with images of contracts, deals, and the severely limited agency such free-market structures, contrary to classic liberal precepts, grant their signers. Analyzing elements of five novels – Gravity's Rainbow, Vineland, Mason & Dixon, Against the Day, and Inherent Vice – this article argues that reading for contracts in Pynchon reveals his deep skepticism of the democratic ideals of social contract theory. The article situates the post- Gravity's Rainbow work in relation to the dismantling of the New Deal's social contract and the privatising contractual schemes endemic to neoliberal governance and offers ways of linking together Slothrop, Vineland 's ex-radicals, Mason and Dixon, the Chums of Chance, and others as figures undone by contracts. Despite all this pessimism about contracts, the article also concludes, though, that Pynchon persistently deploys the trope both to suggest metafictional ideas about artistic freedom and, more importantly, to give renewed texture to his much-discussed motif of broken and unfulfilled American promises.